1975
DOI: 10.1007/bf00357545
|View full text |Cite
|
Sign up to set email alerts
|

messenger RNA-containing ribonucleoprotein from mitochondrial polyribosomes of rat liver

Abstract: A ribonucleoprotein was released from carefully purified rat liver mitochondrial polyribosomes after dissociation with 1 M potassium chloridepuromycin. This ribonucleoprotein was characterized by a sedimentation coefficient ranging from 10-14 S and buoyant density of 1.48 g cm(-3) in cesium chloride equilibrium centrifugation differing in these parameters from the subunits of mitochondrial ribosomes. Poly(A)-containing RNA constituted more than 30% of the total RNA content in this non-ribosomal ribonucleoprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1976
1976
1978
1978

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…These results provide definitive evidence for the existence of discrete po!y(A)-lacking mRNAs in Ehrlich ascites mitochondria. In keeping with our previous (Avadhani et al, 1974) and present findings, Kisselev et al (1975) have recently shown that only about 30% of RNA released from rat liver mt polysomes bind to oligo(dT)-cellulose implying that the rest of the mRNAs may lack poly(A).…”
Section: Discussionsupporting
confidence: 93%
“…These results provide definitive evidence for the existence of discrete po!y(A)-lacking mRNAs in Ehrlich ascites mitochondria. In keeping with our previous (Avadhani et al, 1974) and present findings, Kisselev et al (1975) have recently shown that only about 30% of RNA released from rat liver mt polysomes bind to oligo(dT)-cellulose implying that the rest of the mRNAs may lack poly(A).…”
Section: Discussionsupporting
confidence: 93%
“…Polysomes Qf eukaryotic cells can be dissociated in various ways: in vivo by incubating cells with puromycin (2,3,4), in aminoacid depleted media (5), at elevated temperature (6), under hypertonic conditions (7,8), in the presence of dimethyl sulfoxide (9), in vitro by incubating polysomes with EDTA (10,11,12,13,14,15), under conditions where ribosomes run off the mRNA without reinitiation (16,17), with puromycin at high salt concentration (18,19,20). Wherever it has been tested such dissociations of polysomes have been shown to release mRNA in the form of ribonucleoprotein particles.…”
Section: Introductionmentioning
confidence: 99%
“…Isolation of mitochondria. 1iitochondria were isolated as described (10) and treated with digitonin to remove cytoplasmic contaminations (11).…”
Section: Materiai3 and Methodsmentioning
confidence: 99%